EFEKTIVITAS BAHAN AJAR DIGITAL BERBASIS MOBILE LEARNING PADA PROGRAM STUDI PENDIDIKAN GEOGRAFI UNIVERSITAS TADULAKO - Zumrotin Nisa; Nurvita Nurvita; Rendra Zainal Maliki (Jurnal PIPSI (Jurnal Pendidikan IPS Indonesia), 2022)
The development of Industry 4.0 in the learning process can support graduate learning outcomes. The lecture system both online and offline as well as blended learning can be carried out properly if it is prepared according to learning needs. The learning process in the geography education study program after the 28 September 2018 natural disaster continued with the covid 19 pandemic and the new normal, so the learning process was carried out online and blended learning. This study aims to determine the effectiveness of using digital teaching materials based on mobile learning in geography education study programs. The research design is Quasi Experimental with the Noneequivalent Control Group Design model. All students of the Indonesian regional geography course were the research subjects with a research sample of 2 classes as the experimental class and the control class. This research was conducted in two stages, namely (1) product development of digital teaching materials based on mobile learning and (2) implementation in the LMS class to determine the effectiveness of digital teaching materials based on mobile learning. The research instruments were in the form of tests and questionnaires. N-Gain analysis technique to measure the effectiveness of product development based on student learning outcomes. The results showed 1) Validation by design and instructional media experts showed an average percentage of 76.89% was in the eligible/usable qualifications and the product development attracted student learning interest with a percentage of 79.37%. The results showed that the average level of students' understanding increased as indicated by the average value of the pretest in the experimental class of 47.62 in the control class of 54.29 and the average post-test in the experimental class of 74.29 in the control class of 72.38. Product development is effective for use with an N-gain score for the experimental class of 0.6 and the control class of 0.4 in the medium category.